Patient Experience Performance at a Primary Cancer Center Versus Affiliated Community Facilities - Daniel C. Ma, MD; Abhiram Singh; Beatrice Bloom, MD; Nilda Adair, RTT; William Chen, MD; Husneara Rahman, PhD; Louis Potters, MD; Bhupesh Parashar, MD, DrPH (Advances in Radiation Oncology, 2023)
Purpose: Patient experience tools are used throughout health care to evaluate physician and departmental performance. In radiation medicine, these tools are important in evaluating patient-specific metrics throughout their care journey. This study compared patient experience outcomes from a central tertiary cancer program with network clinics in a health care network. Methods and Materials: Radiation medicine patient experience surveys (Press Ganey, LLC) were collected from a central facility and 5 network locations from January 2017 through June 2021. Surveys were distributed to patients after treatment completion. The study cohort was divided into the central facility and satellites. Questions were converted to a 0 to 100 scale from the Likert scale (1-5). To compare scores between site types, 2-way analysis of variance tests for the significance of sites adjusted for years of operations and adjustments for multiple comparisons (Dunnett's test) were completed on each question. Results: The number of consecutively returned surveys analyzed was 3777; a response rate of 33.3% was observed. The central site conducted 117,583 linear accelerator, 1425 Gamma Knife, 273 stereotactic radiosurgery, and 830 stereotactic body radiation therapy procedures. All satellites combined conducted 76,788 linear accelerator, 131 Gamma Knife, 95 stereotactic radiosurgery, and 355 stereotactic body radiation therapy procedures. The central facility fared better than the satellites on “Convenience of parking” (95.9 vs 87.9; P = .0001) but worse in other domains of care. Conclusions: All sites yielded exemplary patient experience rates. Community clinics scored higher than the main campus. The higher scores at the network sites require a deeper analysis of factors influencing the central facility, as the survey did not account for varying patient volumes and disparities in care complexity across sites. Attributes to satellites include lower patient volumes and easily navigable layouts. These results counter the impression that increased resources at the main campus create a better patient experience relative to network clinics and suggest that high-volume tertiary facilities will require unique initiatives to improve the patient experience.